On a mathematical model of the theory of reliability - Pho, Nguyen Van (Vietnam Journal of Mechanics, 1985)
In the paper a mathematical model of the theory of reliability for structures is considered. The problem of reliability is formulated in stochastic programming forms and Corresponding algorithms are given.